KEARIFAN LOKAL DALAM NOVEL KASONGAN(SEBUAH KAJIAN ANTROPOLOGI SASTRA) - Nilam Sari, Tiara (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aimed to describe and assess the values of local wisdom contained in Kasongan novel written by Budi Santoso Satmoko. This research includes the values of local wisdom that such beliefs, customs, traditional food that can be useful for the reader. This study used descriptive qualitative research method, by taking and classifying data according to the codification table. And, the results of this study indicate that Indonesia has a cultural diversity within each community. Through research Local wisdom is contained in the culture of local communities can be known through literature containing the values of local wisdom. The values of local wisdom contained in the novel Kasongan Satmoko work Budi Santoso, can be used as a mirror to preserve local culture.